KETERLIBATAN INDONESIA DENGAN BRICS: ANTARA KEBIJAKAN LUAR NEGERI YANG BEBAS DAN AKTIF SERTA KETERLIBATAN STRATEGIS YANG TERBATAS - Indah Dian Nurani Siregar; Ali Maksum (Universitas Jenderal Ahmad Yani, 2025)
This study aims to analyze Indonesia’s national interests in its post-2025 membership in BRICS by employing the national interest framework, particularly classical realism. BRICS has evolved into a strategic alliance of emerging economies that exerts significant influence in the multipolar world order. However, to date, there has been no specific study examining Indonesia’s position after formally joining BRICS, either from the perspective of foreign policy or national interest. Drawing on a literature-based method, this research reviews 85 Scopus-indexed journal articles (2020–2025), international media reports, and official government documents. The findings demonstrate that Indonesia’s membership in BRICS reflects a rational effort to pursue vital and strategic interests, such as securing alternative financing through the BRICS New Development Bank (NDB), enhancing diplomatic influence in the Global South, and diversifying external partnerships. Within the framework of the “free and active” foreign policy.